1867 Ariz. Sess. Laws 21 - (:unkn) unknown (My University, 1867)
Prohibited brandishing in a rude or threatening manner, any dirk, dirk-knife, Bowie-knife, pistol, gun, or other deadly weapon. Also prohibited fighting or quarrelling with the same. Violators fined not less than one hundred but no more than five hundred dollars, or imprisoned not less than one but no more than six months, or both.
Keywords: BRANDISHING